Accuracy of GNSS Methods - Ugur Sanli, Dogan (IntechOpen, 2019)
Following the GPS, new GNSS techniques are emerging today. Various surveying and processing methods are available for the analysis of GNSS data. Equipment and software are also varied. The orbit quality, controlled by the system designer, and the IGS are continuously improved. The user is mainly interested in the quality of position and of the deformation rates produced by the GNSS. Hence, research needs to guide the user in terms of selecting the best combination of the available methods and instrumentation to produce the desired accuracy. This book reviews the current available accuracy obtainable using the GNSS methods. In fact, the main aim of this book is to make an impact on young researchers so that they keep updating the accuracy of GNSS for future generations.